Iodide‐Catalyzed Phosphorothiolation of Heteroarenes Using P(O)H Compounds and Elemental Sulfur. Issue 13 (7th May 2019) - Shi, Shanshan; Chen, Jun; Zhuo, Shaohua; Wu, Zi'ang; Fang, Meijuan; Tang, Guo; Zhao, Yufen
Abstract: Organothiophosphates have found widespread application as biologically active compounds and synthetic intermediates in medicinal chemistry. The first transition‐metal‐free one‐pot direct synthesis of heterocyclic phosphorothioates involving indole or imidazo[1, 2‐a]pyridine derivatives, elemental sulfur, and P(O)H compounds is presented. The use of NaI or KI as a catalyst, tert ‐butyl hydroperoxide as an oxidant, various indole and imidazo[1, 2‐a]pyridine derivatives are tolerant in this transformation, affording the corresponding products in good to excellent yields. Moreover, this method can be easily adapted to large‐scale preparation. O, O ‐Diethyl S ‐(1‐phenyl‐1H‐indol‐3‐yl) phosphorothioate presents potent anti‐inflammatory activity in lipopolysaccharide (LPS)‐stimulated RAW264.7 cells in a dose‐dependent manner. Abstract :